Rational solutions from Pade approximants for the generalized Hunter-Saxton equationa - Aratyn, H.; Gomes, J. F. [UNESP]; Ruy, D. V. [UNESP]; Zimerman, A. H. [UNESP]; Burdik, C.; Navratil, O.; Posta, S. (Iop Publishing Ltd, 2013)
Exact rational solutions of the generalized Hunter-Saxton equation are obtained using Pade approximant approach for the traveling-wave and self-similarity reduction. A larger class of algebraic solutions are also obtained by extending a range of parameters within the solutions obtained by this approach.